Sobbing - Phonotherapeutic Characteristics and Possibilities - Cardoso, Maria Cristina de Almeida Freitas; Xavier, Andiara Cristina Furtado (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Sobbing is a reflex action that occurs because of a diaphragmatic spasm at the moment of the inspiration with the simultaneous glottic closure, followed by a characteristic noise. In our clinical practice we have found patients who begin to present with persistent sobbing after a neurologic clinical event.Objective: To characterize sobbing, establish its etiology and therapeutic possibilities.Method: A bibliographic review of data published in the last 10 years, whose descriptors include: Sobbing, sobbing and stomatognatic system, sobbing and treatment.Final Comments: Based on the data of the literature, we concluded that sobbing may occur in view of the neurological pathologies, gastrointestinal, thoracic and/or toxic metabolic profiles The treatment forms are related to the forms of sobbing that can be benign, by interruption of the breathing cycle, or persistent, through pharmacological and/or surgical medical procedures, in addition to the use of acupuncture. Depending on its frequency and speed, we presume that it may change the functions of deglutition, breathing and speech, because the pneumo-phono-articulatory organs and the mechanisms in charge of such functions change in view or this event, and cause abnormalities to its functionality, which makes us refer to a possible phonoaudiological therapeutic approach.
Keywords: sobbing; deglutition; breathing; phonoaudiology